Coal - Coal Washing in Colorado and New Mexico - J. D. Price; W. M. Bertholf (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1950)
In preparing a paper on coal washing in Colorado and New Mexico, it is difficult to refrain from entering into a discussion of the historical aspects of this subject, for the story of coal washing in these states goes hack well into the last century. This phase of the subject could well make a complete paper in itself, and of necessity this present discussion must be limited to current operations. Therefore, we are taking into consideration only those washing plants which have operated for some period during the years of 1947 and 1948. Summary Of the eight million tons of coal mined in the two states in 1947. ap- proximately two million tons were washed in wet washing plants, using concentrating tables or jigs. The one table plant accounted for 70 pct of the output of washed coal, and two large Baum jig plants accounted for an additional 26 pct, leaving only a small residual tonnage to be accounted for by other types of jigs The necessity for washing coal is occasioned by the desire or necessity of reducing the ash content of the coals— sulphur is not a problem in this area. All washeries, except the table plant, are at or near the tipple, hence wash only one kind of coal. At the table plant a large number of different coals are washed. Only at the table plant is there any occasion for drying any considerable quantity of fine coal— other plants size and/or dewater on shaking screens. The results of washing at the smaller plants are judged by the number (or lack) of complaints about the quality of the washed coal. This is probably as good a system as can he devised for small, intermittent operations. The efficiency of the Baum jig ap-pears to be quite high. This is to be expected as long as the automatic control of the refuse gate operates properly. The efficiency of the concentrating table is not as high as that of the Baum jig, especially when the "difficulty" of washing is taken into consideration. When dealing with coals in which the "bone" is larger than the "coal," the table appears to be at a definite disadvantage, because of its sizing action.